Implementasi Google Sites JENUSA Untuk Meningkatkan Pemahaman Kedatangan Bangsa Asing pada Siswa Kelas VI : Penelitian - Shintyasari Hadi Karmila; Meri Sulistia; Meutia Zuniar; NG. Shofi Isis Cofia; Rifa Rodhiyatan Mardhiyyah; Rana Gustian Nugraha (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to improve the understanding of sixth-grade students of SDN Mandalaherang III on the material of the Arrival of Foreign Nations to Indonesia through the implementation of the digital learning media Google Site JENUSA. This study uses the Action Research method with a mixed-methods in two cycles. Each cycle consists of planning, action, observation, and reflection. The research subjects were 31 students and data were collected through learning outcome tests (quantitative) and observation of learning activities (qualitative). The results showed that in cycle I, after using basic Google Site, students' understanding increased with an average post-test of 78.06 and classical completion of 64.51%, but the implementation was not optimal. Based on reflection, the learning media in cycle II was enriched with the integration of interactive PowerPoint to clarify the flow of events. As a result, there was a significant increase with an average post-test of 90.32 and classical completion reaching 96.77%. Observations also noted an increase in student activeness and ability to explain the material coherently. Thus, the implementation of the JENUSA Google Site enriched with interactive content has proven effective in increasing students' understanding of the Arrival of Foreign Nations to Indonesia.